2020
DOI: 10.1016/s0140-6736(20)31790-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of trimetazidine after percutaneous coronary intervention (ATPCI): a randomised, double-blind, placebo-controlled trial

Abstract: The efficacy and safety of trimetazidine in patients having been treated by percutaneous coronary intervention (ATPCI): Results of a randomised double-blind placebo-controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 18 publications
1
22
0
5
Order By: Relevance
“…In addition, this trail also showed there were no statistically significant differences in thrombocutopenia, agranulocytosis, hepatic disorders, etc. between treatment groups (Ferrari et al, 2020).Therefore, trimetazidine is relatively safe even in long-term prescription.…”
Section: Adverse Effectsmentioning
confidence: 96%
“…In addition, this trail also showed there were no statistically significant differences in thrombocutopenia, agranulocytosis, hepatic disorders, etc. between treatment groups (Ferrari et al, 2020).Therefore, trimetazidine is relatively safe even in long-term prescription.…”
Section: Adverse Effectsmentioning
confidence: 96%
“…TMZ treatment signi cantly activates AMPK and ERK signaling pathway, and inhibits MMP-2 and MMP-9 expression, which leads to a reduction of oxidative stress in ischemia-reperfusion hearts [5,21]. All of the above mechanisms may contribute to reducing the infarction size for STEMI Some previous researches show no signi cant improvement of TMZ on the prognosis of angina pectoris after recent successful PCI [24]. However, a meta-analysis has reported that early TMZ therapy had overall bene ts upon total MACEs in patients with AMI [12].…”
Section: Discussionmentioning
confidence: 99%
“…Por ello, la ATC ha demostrado ser una prueba diagnóstica anatómica capaz de tener un impacto clínico en el manejo de pacientes con SCC, antianginoso al mejorar los síntomas; no obstante, su beneficio en la reducción de complicaciones cardiovasculares es discutible (6) . Como manejo de segunda línea están los nitratos, ivabradina, ranolazina, nicorandil (27)(28)(29) o la trimetazidina; sin embargo, esta última utilizada a una dosis de 35 mg dos veces al día, posterior a una ICP exitosa, no logró influir en la recurrencia de angina ni en el desenlace primario (muerte, hospitalización por causa cardiaca) (30) .…”
Section: Diagnósticounclassified